2013
DOI: 10.1136/sextrans-2013-051166
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance monitoring inNeisseria gonorrhoeaeand strategic use of funds from the Global Fund to set up a systematic Moroccan gonococcal antimicrobial surveillance programme

Abstract: Following these results the Ministry of Health of Morocco replaced ciprofloxacin and introduced ceftriaxone 250 mg as a single dose in the treatment of gonococcal infections. Using funds from the Global Fund to Fight AIDS, Tuberculosis and Malaria (the Global Fund), a surveillance programme was set up for antimicrobial resistance testing in N gonorrhoeae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…While a recent study from Morocco reported that a total of 72 isolates were examined, and a significant resistance to tetracycline (92.8%) and ciprofloxacin (86.8%), which were used as first-line treatment in gonococcal infections in Morocco. However, no resistance was found to spectinomycin, ceftriaxone or cefixime in all the isolates [36].…”
Section: Antimicrobial Treatmentmentioning
confidence: 80%
See 1 more Smart Citation
“…While a recent study from Morocco reported that a total of 72 isolates were examined, and a significant resistance to tetracycline (92.8%) and ciprofloxacin (86.8%), which were used as first-line treatment in gonococcal infections in Morocco. However, no resistance was found to spectinomycin, ceftriaxone or cefixime in all the isolates [36].…”
Section: Antimicrobial Treatmentmentioning
confidence: 80%
“…The emergence of fluoroquinoloneresistant N. gonorrhea in the United States prompted the CDC in 2007, to stop recommending fluoroquinolones for treatment of gonorrhea, leaving cephalosporins as the only remaining class of antimicrobials available for treatment of gonorrhea in the United States [36]. Criteria for resistance to cefixime and cef- Because of the prevalence of tetracycline resistance among N. gonorrhea isolates worldwide, particularly those with elevated cefixime MICs, the use of azithromycin as the second antimicrobial is preferred.…”
Section: Antimicrobial Treatmentmentioning
confidence: 99%
“…[3] Further, these estimates can be utilized in the assessment of the global trends and to ensure comparison between various nations. [345] Moreover, it has been advocated that any nation which can ascertain and then only provide appropriate therapeutic care can significantly address the problem of gonorrhea. [45] In addition, a simultaneous improvement in the existing STI package of services, better emphasis on behavior alterations and compliance with the treatment guidelines, and ensuring involvement of the community in different stages of the program can play a significant role in enhancing the utility of the services.…”
mentioning
confidence: 99%
“…[5] Over the years, this programme has been launched across various European nations, United States of America, and Morocco to streamline the extent of the problem and alter the treatment guidelines at the right time. [567]…”
mentioning
confidence: 99%
“…[5] The generated data will simultaneously assist the WHO in monitoring the global trends and comparing the situation in different regions of the world. [567] The generated reports can be utilized by the policy makers from India as well, and necessary modifications in the existing policies can be made for containing the problem of antimicrobial resistance. [567]…”
mentioning
confidence: 99%